Clinico-Haematological, Biochemical And Therapeutic Studies On Nutritional Anaemia In Goats (Applied Biological Research, 2011)
A significant decrease in haemoglobin, packed cell volume, total  erythrocyte count, mean corpuscular volume, mean corpuscular  haemoglobin and biochemical indices [total serum protein, albumin,  globulin, albumin-globulin (A:G) ratio and blood glucose] and serum  trace minerals (copper, cobalt and iron) were observed in eight goats  showing the symptoms of anaemia and emaciation. Blood examination of  anaemic goats revealed microcytic hypochromic anaemia. The anaemic  goats were treated with an iron preparation injection Feritas (Intas Pharmaceuticals Ltd., India) @ 1 ml per animal intra-muscularly. Second  and third injection was repeated 3 days each after first dosing. Along  with parenteral therapy the anaemic goats were also given Ayumin V5 mineral mixture (Dabur Ayurvet Pvt. Ltd., India) @ 10 g daily to each  goat for 30 days to supplement the micronutrients. The therapeutic  response to iron preparation with oral haematinics resulted in significant  improvement in haemogram of goats suffering from anaemia. Total  serum protein and blood glucose also increased significantly after treatment. Significant improvement in serum copper, cobalt and iron  level was observed after treatment. It can be concluded that the use of  oral and parentral haematinics is very effective in treating the nutritional anaemia in goats.
Keywords: Anaemia; blood profile; goats; therapeutic response